Polluted Online Reviews: The Effect of Air Pollution on Reviewer Behavior. Issue 4 (2nd October 2019) - Fang, Jiaming; Hu, Lixue; Hossin, Md Altab; Yang, Jingjing; Shao, Yunfei
ABSTRACT: Studying how weather conditions might relate to customer ratings and reviews represents a research lacuna, even though anecdotal evidence suggests that weather is likely to influence the reviewer behavior. Building on affect theories, the present research combines two complementary methodologies to investigate whether and how the levels of air quality influence customers' online numeric ratings and review-writing behaviors. The results of econometric analysis based on a large-scale daily review data set obtained from a restaurant review site reveal that customers are more prone to provide relatively lower numeric ratings when they are exposed to a high-pollution environment. Also, the customers are reluctant to expend time and effort in writing detailed and vivid reviews on high air pollution days. The subsequent randomized controlled experiment further confirms the causal effect of psychologically experiencing an air pollution situation on decreased rating scores by showing that the feelings of anxiety and psychological aggressiveness serially mediate the effect. This study is the first to empirically establish the link between air quality and review bias, and the findings suggest that merchants should integrate air quality information into their online review management strategies and provide incentives to stimulate reviewers to write high-quality reviews on high air pollution days.